2012
DOI: 10.1021/jf3008713
|View full text |Cite
|
Sign up to set email alerts
|

NMR Characterization of Saccharides in Italian Honeys of Different Floral Sources

Abstract: The saccharide profiles of 5 different botanical species in 86 Italian honey samples were investigated by ¹H and ¹H-¹³C NMR spectroscopy. Nineteen saccharides were identified in the aqueous extracts, namely, fructose, glucose, gentiobiose, isomaltose, kojibiose, maltose, maltulose, melibiose, nigerose, palatinose, sucrose, turanose, erlose, isomaltotriose, kestose, maltotriose, melezitose, raffinose, and maltotetraose. PCA performed on NMR spectral regions, in particular between 4.400 and 5.700 ppm and the fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 31 publications
4
44
1
1
Order By: Relevance
“…The complexity of NMR data in food metabolomics studies is clearly the primary impetus for the coupling of NMR spectroscopy with multivariate statistical methods, capable of gathering samples with similar features Tomassini, Capuani, Delfini, & Miccheli, 2013). Among them, supervised methods that may enhance classification performance, such as orthogonal projection to latent structures -discriminant analysis (OPLS-DA) and its bidirectional modifications (O2PLS-DA) (Bylesjö, Rantalainen, Cloarec, Nicholson, Holmes, & Trygg, 2006), have shown great potential to determine the authenticity of various foodstuffs, mainly on the basis of their geographical or botanical origin (Consonni, Cagliani, & Cogliati, 2012a, 2012bConsonni, Cagliani, Stocchero, & Porretta, 2009Fotakis et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The complexity of NMR data in food metabolomics studies is clearly the primary impetus for the coupling of NMR spectroscopy with multivariate statistical methods, capable of gathering samples with similar features Tomassini, Capuani, Delfini, & Miccheli, 2013). Among them, supervised methods that may enhance classification performance, such as orthogonal projection to latent structures -discriminant analysis (OPLS-DA) and its bidirectional modifications (O2PLS-DA) (Bylesjö, Rantalainen, Cloarec, Nicholson, Holmes, & Trygg, 2006), have shown great potential to determine the authenticity of various foodstuffs, mainly on the basis of their geographical or botanical origin (Consonni, Cagliani, & Cogliati, 2012a, 2012bConsonni, Cagliani, Stocchero, & Porretta, 2009Fotakis et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, liquids such as fruit juices, wines and honeys can be easily examined by NMR . Italian honeys were successfully classified based on their NMR spectra and multivariate statistical analysis . It was suggested that the sugar profile could be used to characterize particular honey samples.…”
Section: Introductionmentioning
confidence: 99%
“…Included in the review are a survey of 21 common food polysaccharides, the current understanding of their structures, and the techniques used for their determination. In 2012, Consonni et al [152] characterized the profile of 5 different botanical species in 86 Italian honey samples by 1 H and 1 H-13 C NMR spectroscopy. They recognize and identify 19 saccharides in the aqueous extracts and suggest that the saccharides contest could be employed to characterize honey samples and to construct an identity card of saccharides for each floral source.…”
Section: Nmr Development In Carbohydrate Impurities Profilingmentioning
confidence: 99%